Makna, Konsekuensi Jurisprudensi, dan Korelasi Kata Awliyā’ Perspektif Abū Bakr Jābir al-Jazā’irī dalam Kitab Aysar al-Tafāsīr - Samani, Samani (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
Abstract: Controversy surrounding the meaning of Q.S. al-Māidah [5]: 51 regarding whether or not a non-Muslim leader in Indonesia is a hot issue nowadays. The pros and cons around whether or not non-Muslim leaders are widely discussed by academics in Indonesia. The article elaborates the term awliyā’ in surah al-Mā’idah [5]: 51 focusing specifically on Abū Bakr Jābir al-Jazāirī’s perspectives in his Aysar al-Tafāsīr. In addition, it discusses jurisprudential consequence of the term and its correlation to other terms such as khalīfah, mulk, imāmah, amīr al-mu’minīn, and sulṭān. The study finds that the term awliyā’ has correlation of meaning to other terms concerning leadership, particularly the aforement-ioned five terms. Although each term possesses its own denotative meaning, all of these terms connotatively contain correlative synonym and similar meaning, not that of paradigmatic and controversial meaning. All of them refer to similar meaning, i.e. leadership and power.